(untitled) (AYUSHDHARA, 2025)
Hormones significantly influence a woman’s life, from menarche to menopause. Imbalances in ovarian hormones, in conjunction with the hypothalamic-pituitary-ovarian (HPO) axis, can impact her physical, psychological, and reproductive health. Poor dietary habits and altered lifestyle choices can affect the secretion of female hormones, potentially leading to the development of ovarian cysts. Hemorrhagic ovarian cysts are commonly encountered in routine gynecological practice. Methodology: In this present case study, a 28 years old female patient consulted to the OPD with the complaint of irregular and scanty menses, anxious to conceive. Ultrasonography (USG) findings suggested a right ovarian haemorrhagic cyst measuring 42X39X32mm (28.9cc). She was treated with traditional ayurvedic formulations on the basis of Granthi nashak chikitsa; with the goal of relieving symptoms and dissolving the ovarian cyst. This patient was treated with formulations i.e., Ajmodadi churna, Kanchnar guggulu, Dashmoolarishta, Kumaryasava, Chitrakadi vati for two months. Result: Traditional Ayurvedic treatments were employed throughout the course of the therapy. Follow-up ultrasonography (USG) revealed a complete resolution of the cyst, and the symptoms significantly subsided. Conclusion: This study highlights the effectiveness of Ayurveda in achieving positive outcomes in the management of ovarian cysts.